Fibromatosis colli: a case series of three infants - Gupta, Sunny; Kankane, Vivek; Shukla, Avdhesh; Sharma, Avinash (International Journal of Research in Medical Sciences, 2025)
Fibromatosis colli is a rare, benign fibrous lesion of the sternocleidomastoid muscle in infancy. It typically presents as a firm; non-tender neck swelling within the first few weeks of life and is strongly associated with birth trauma. We report a series of three infants with fibromatosis colli, emphasizing the role of clinical evaluation, ultrasonography, and fine-needle aspiration cytology (FNAC) in diagnosis, with physiotherapy as the mainstay of management. A four-week-old male presented with a left cervical swelling following breech delivery. Ultrasound showed fusiform thickening of the left sternocleidomastoid, and FNAC confirmed fibromatosis colli. He was managed conservatively with physiotherapy. A six-week-old female presented with right-sided neck swelling after a forceps-assisted delivery. Ultrasound revealed an ellipsoid enlargement of the right sternocleidomastoid, and FNAC showed spindle fibroblastic cells. She responded well to physiotherapy with near-complete resolution at three months. A three-week-old male had bilateral sternocleidomastoid thickening with restricted neck movement after prolonged labor. Ultrasound confirmed bilateral fusiform thickening, and FNAC ruled out malignancy. Physiotherapy led to gradual improvement over 4 months. Early recognition of fibromatosis colli is crucial to avoid unnecessary investigations and parental anxiety. Timely physiotherapy results in spontaneous regression in most cases, while surgery is reserved only for refractory cases.